Symmetric naphthalenediimidequaterthiophenes for electropolymerized electrochromic thin films1. Issue 23 (21st June 2015) - Figà, V.; Chiappara, C.; Ferrante, F.; Casaletto, M. P.; Principato, F.; Cataldo, S.; Chen, Z.; Usta, H.; Facchetti, A.; Pignataro, B.
<x xml:space="preserve">Abstract</x> Novel electropolymerized copolymers with a controlled donor/acceptor ratio obtained from symmetric naphthalenediimidequaterthiophene showed prominent physico-chemical properties and high coloration efficiency in electrochromic devices.